Effect Of Isometric Exercises Using an Active Therapeutic Movement Device for Patients with Acute Low Back Pain (International Journal of Physiotherapy, 2022)
Background: This study aimed to investigate the effects of isometric exercise using ATM®2 for acute low back pain (LBP) patients as a flexion or extension type.Methods: The subjects were twenty individuals (age 39.7±8.0ys, 12 males / 8 females) with acute LBP of less than four weeks duration who volunteered to participate in the study. The participants were allocated into four groups. First, the participants were classified by the direction of the movement causing pain in flexion and extension types. Secondly, both types were allocated randomly into two groups which were given exercises using the ATM®2 group and the usual care group. Finally, both groups were treated three times weekly for two weeks, totaling six sessions.Results: In terms of the extension type of LBP, the effect of the extension pain in the ATM®2-group significantly decreased pain (p=0.04) immediately. And in both groups significantly decreased (p=0.01, 0.001) for two weeks of intervention. Furthermore, in the flexion type of LBP, the effect of the flexion pain in the ATM®2-group and usual care group significantly decreased (p=0.001, p=0.03) during the two weeks intervention. However, neither group had an immediate effect.Conclusion: Isometric exercise using ATM®2 may have an immediate and short-term effect on acute LBP, which is greater in patients with an extension-type pattern. The ATM®2 exercise may reduce the pain of the acute LBP. Furthermore, it will be a problem in the future to analyze if the influence of pain is reduced in the immediate natural period that gives to chronic LBP.